Cluster of symptoms in kidney failure: A systematic review - Gomariz-Ruiz, Jaime; Pérez-Cruzado, David Francisco; Gutiérrez-Sánchez, Daniel (Elsevier, 2024)
Background Chronic kidney disease is a global problem characterized by a progressive decrease in kidney function with associated symptoms. A better understanding of these symptoms could lead to the development of personalized strategies. Objective This systematic review aims to describe the clusters of symptoms in kidney failure and categorize them according to their time of onset and how disabling they are for patients. Design A systematic review was carried out. Methods This systematic review was conducted according to the PRISMA declaration standards. The search engines used were initially limited to WOS, Embase, and PubMed, and they were employed between November 2022 and January 2023. In addition, the bibliographic search was supplemented with databases of the grey literature, such as OpenGrey, in May 2023. The following inclusion criteria were established: cross-sectional studies, studies on adult populations, and studies dealing with clusters of symptoms associated with kidney failure. Before an article was definitively selected, the checklist of the STROBE initiative, with a maximum of 22 points, was applied, assessing the quality of cross-sectional articles. Articles were selected independently and blinded by two researchers, and a third researcher was involved in case of disagreement. Results After carrying out the bibliographic search, we found that eight articles, out of the 46 articles that were evaluated, fully met the inclusion criteria. Two tables were made, which include important information, such as the participants’ profiles or the way the authors extracted a cluster of symptoms. Limitations The main area for improvement is that it was not possible to perform a meta-analysis due to the methodology used in the articles analysed. Constraining the selection of articles to those written in Spanish or English could be a limitation as not all articles dealing with symptom clusters in kidney failure were considered.
Keywords: Insuficiencia renal crónica; Kidney failure; Symptom cluster; Chronic kidney disease; Systematic review